Role of the Open‐Shell Character on the Pressure‐Induced Conductivity of an Organic Donor–Acceptor Radical Dyad. Issue 21 (24th March 2018) - Souto, Manuel; Gullo, Maria Chiara; Cui, HengBo; Casati, Nicola; Montisci, Fabio; Jeschke, Harald O.; Valentí, Roser; Ratera, Imma; Rovira, Concepció; Veciana, Jaume
Abstract: Single‐component conductors based on neutral organic radicals have received a lot of attention due to the possibility that the unpaired electron can serve as a charge carrier without the need of a previous doping process. Although most of these systems are based on delocalized planar radicals, we present here a nonplanar and spin localized radical based on a tetrathiafulvalene (TTF) moiety, linked to a perchlorotriphenylmethyl (PTM) radical by a conjugated bridge, which exhibits a semiconducting behavior upon application of high pressure. The synthesis, electronic properties, and crystal structure of this neutral radical TTF‐Ph‐PTM derivative (1 ) are reported and implications of its crystalline structure on its electrical properties are discussed. On the other hand, the non‐radical derivative (2 ), which is isostructural with the radical1, shows an insulating behavior at all measured pressures. The different electronic structures of these two isostructural systems have a direct influence on the conducting properties, as demonstrated by band structure DFT calculations. Abstract : A non‐planar and spin localized radical based on a tetrathiafulvalene (TTF) moiety and linked to a perchlorotriphenylmethyl (PTM) radical by a conjugated bridge has been developed, which exhibits a semiconducting behavior upon application of high pressure. In contrast, the isostructural non‐radical derivative shows an insulating behavior at all measured pressures. The different electronic structures of these two isostructural systems have a direct influence on the conducting properties, as demonstrated by band structure DFT calculations.